The American tradition in literature. Volume 2 - Perkins, George; Perkins, Barbara (Estados Unidos: Mc Graw Hill, 2002)
An age of expansion - New voices in poetry: Walt Whitman, Emily Dickinson, Sidney Lanier - Crosscurrents: Freedom and the gilded age: Walth Whitman, Henry Adams, George Wahington, Booker T. Washington - Realists and regionalists: Louisa May Alcott, Mark Twain, William Dean Howells, Henry James, Bret Harte, Red Cloud, Sarah Winnemucca Hopkins, Ambrose Bierce, George Washington Cable, Joel Chandler Harris - The turn of the century: Henry Adams, Sarah Orne Jewett, Kate Chopin, etc.
Incluye referencias bibliogràficas.
Incluye ìndice.
Keywords: Literatura Norteamericana; Poesía